METHODOLOGICAL PROBLEMS OF STATISTICAL CALCULATIONSOF MACROECONOMIC INDICATORS - E.P. Vasilyev (European Scientific Journal, ESJ, 2014)
The paper highlights the basic issues in the area of statistical methodology of calculations of macroeconomic indicators. In particular, it is proved that a single, internally consistent methodology and methods of the GDP calculation do not exist. Moreover, current methodology and methods of the GDP calculation have significant drawbacks. From the point of view of the theory of cycles of resources self-renewal which is still developing, both theoretically and practically, modern methods of the GDP calculation do not reflect the final results of such a complex system as the economy is. From our viewpoint, in order to reflect adequately the final results of the economic system as a whole it is necessary to use such indicators as: - Gross increase in all types of resources in all sectors of the economy for Δt; - Net increase in stocks of all kinds of resources for Δt.